Thyroid autoimmunity at onset of type 1 diabetes as a predictor of thyroid dysfunction: a thirty-years retrospective longitudinal study - Carreras, Gemma; Mendoza, Lilian C.; Colom, Cristina; Tirado-Capistros, Mireia; Sardà, Helena; Sánchez-Quesada, José Luis; Pérez, Antonio (Frontiers in Endocrinology, 2025)
BackgroundThyroid autoimmunity commonly coexists with type 1 diabetes due to shared autoimmune mechanisms, and early recognition of thyroid dysfunction is crucial for optimizing metabolic control. However, there is no consensus regarding the optimal screening strategy for detecting thyroid disease in patients with type 1 diabetes. This study aimed to determine the long-term predictive value of thyroid peroxidase antibodies (TPO-Abs) at the onset of type 1 diabetes for the development of thyroid dysfunction and to evaluate the influence of age at diabetes onset.MethodsWe conducted a retrospective longitudinal study at a tertiary university hospital in Barcelona, Spain, including 160 Caucasian patients consecutively diagnosed with type 1 diabetes between 1987 and 1994. All participants were followed for at least 10 years (mean follow-up 30.6 ± 4.5 years). TPO-Abs were measured at diabetes onset, and thyroid function was periodically assessed throughout follow-up. The incidence of thyroid dysfunction was analyzed according to TPO-Ab status and age at diabetes onset (<18 vs ≥18 years).ResultsAt diabetes diagnosis, 21.9% of patients were TPO-Abs positive. Antibody positivity was a strong predictor of thyroid dysfunction, conferring an eightfold increased risk compared with antibody-negative patients (RR 8.1, 95% CI 4.79–13.69, p<0.001). During follow-up, thyroid dysfunction also developed in initially antibody-negative patients, particularly in those diagnosed before 18 years of age, whereas cases were rare among those diagnosed in adulthood. The relative risk of thyroid dysfunction associated with TPO-Abs at diabetes onset was substantially higher in adults compared with youth (RR 12.6, 95% CI 6.10–25.81 vs. RR 3.4, 95% CI 1.35–8.71).ConclusionA rational screening strategy for thyroid disease in asymptomatic patients with type 1 diabetes should include measurement of TPO-Abs and thyrotropin at diagnosis, followed by annual thyrotropin assessment in antibody-positive individuals. In patients diagnosed with type 1 diabetes before 18 years of age who are initially antibody-negative, repeat screening every two years from puberty through adulthood is recommended.